Strategies for replica consistency in data grid – a comprehensive survey. (15th July 2016) - Vashisht, Priyanka; Sharma, Anju; Kumar, Rajesh
Summary: Data grid provides an efficient solution for data‐oriented applications that need to manage and process large data sets located at geographically distributed storage resources. Data grid relies on data replicas to enhance the performance and to ensure the fault tolerant results to the users. Replicas are developed to increase the availability of data and to provide better data access. Replicas have their own advantages, but there are a number of issues that must be resolved. Among various existing issues, the critical concern is replica consistency. Various replica consistency strategies are available in the literature. These strategies rationalize and investigate various parameters like bandwidth consumption, access cost, scalability, execution time, storage consumption, staleness, and freshness of replicas. In this paper, several asynchronous replica consistencies are classified and analyzed based on various strategies such as topology, level of abstraction, update propagation, and locality. Some other strategies are also discussed and analyzed like adaptive consistency, quorum‐based consistency, load balancing, and agent‐based economically efficient, check‐pointing, fault tolerance, and conflict management. Parameters on which these strategies are analyzed are methodology, replication classification, consistency, grid topology, environment, evaluation parameters, and performance. Copyright © 2016 John Wiley & Sons, Ltd.